Analisis kualitas soal Ujian Akhir Semester Pendidikan Agama Islam dan Budi Pekerti pada SMPN kota Makassar - Sarea, Muh Syahrul (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
This study aims to describe the characteristics of items and estimate the mistakes of the standard error of measurements of final semester exam questions of Islamic Education subject from two schools namely SMPN 17 Makassar and SMPN 19 Makassar. This research is a quantitative descriptive study with research subjects, namely students who follow the final semester exam of Islamic Education subject while the object of research in the form of student answer sheet documents with a total of 612. The results showed that the difficulty level of items from test items in SMPN 17 Makassar and SMPN 19 Makassar was categorized as suitable for use. The Discrimination Power Index of the test items at SMPN 17 Makassar is categorized as good at 92,5% and not good at 7.5%. In comparison, the test items at SMPN 19 Makassar are categorized as good 100%. The lowest value of the standard error of measurement of final semester exam questions at SMPN 17 Makassar is 0.000173681 and the highest is 26.44767997 while the lowest standard error of measurement value of final semester exam questions at SMPN 19 Makassar is 0.65658735 and the highest is 7.903108528. Abstrak Penelitian ini bertujuan untuk menggambarkan karakteristik butir dan mengestimasi besar kesalahan baku pengukuran soal UAS PAI yang terisi dari dua sekolah, yaitu SMPN 17 Makassar dan SMPN 19 Makassar. Penelitian ini termasuk jenis penelitian deskriptif kuantitatif dengan subjek penelitiannya yaitu, siswa yang mengikuti UAS PAI. Sedangkan objek penelitian berupa dokumen lembar jawaban siswa sebanyak 612. Hasil penelitian menunjukkan bahwa tingkat kesukaran butir soal pada SMPN 17 Makassar dan SMPN 19 Makassar dikategorikan baik untuk digunakan. Indeks daya beda butir SMPN 17 Makassar baik sebesar 92,5% dan tidak baik 7,5%. Sedangkan pada SMPN 19 Makassar yang dikategorikan baik 100%. Besar SEM soal UAS SMPN 17 Makassar terendah adalah sebesar 0.000173681 dan tertinggi adalah sebesar 26.44767997 sedangkan Besar SEM Soal UAS SMPN 19 Makassar terendah adalah sebesar 0.65658735 dan tertinggi adalah sebesar 7.903108528